Thyroid surgery without drain - Aich, Mani Lai; Kamruzzaman, M; Alam, ABM Khorshed; Taous, Ahmmad; Abdullah, M (Bangladesh Journal of Otorhinolaryngology, 2011)
Use of surgical drains after thyroid surgery is standard surgical practice to prevent lifethreatening complications, arising from post-operative haematoma. There is increasing evidence to suggest that this is an outdated practice. This study determines whether thyroid surgery can be safely performed without the routine use of drains. This cross sectional study was done for two years and one hundred thyroidectomies were performed. No drains were inserted in any patient. Complications of thyroid surgery in this series were seroma formation (5%) cases and minor haematoma was only 1%. Re-exploration for bleeding was not encountered in any cases in this series. There is no evidence to suggest the routine use of surgical drains following uncomplicated thyroid surgery. Key words: Thyroid Surgery; Drain DOI: http://dx.doi.org/10.3329/bjo.v17i2.8852 BJO 2011; 17(2): 121-124